Deciphering the photochemical mechanisms describing the UV-induced processes occurring in solvated guanine monophosphate - Altavilla, Salvatore F.; Segarra-Martí, Javier; Nenov, Artur; Conti, Irene; Rivalta, Ivan; Garavelli, Marco (Frontiers in Chemistry, 2015)
The photophysics and photochemistry of water-solvated guanine monophosphate (GMP) are here characterized by means of a multireference quantum-chemical/molecular mechanics theoretical approach (CASPT2//CASSCF/AMBER) in order to elucidate the main photo-processes occurring upon UV-light irradiation. The effect of the solvent and of the phosphate group on the energetics and structural features of this system are evaluated for the first time employing high-level ab initio methods and thoroughly compared to those in vacuo previously reported in the literature and to the experimental evidence to assess to which extent they influence the photoinduced mechanisms. Solvated electronic excitation energies of solvated GMP at the Franck-Condon (FC) region show a red shift for the ππ* La and Lb states, whereas the energy of the oxygen lone-pair nπ* state is blue-shifted. The main photoinduced decay route is promoted through a ring-puckering motion along the bright lowest-lying La state toward a conical intersection (CI) with the ground state, involving a very shallow stationary point along the minimum energy pathway in contrast to the barrierless profile found in gas-phase, the point being placed at the end of the minimum energy path (MEP) thus endorsing its ultrafast deactivation in accordance with time-resolved transient and photoelectron spectroscopy experiments. The role of the nπ* state in the solvated system is severely diminished as the crossings with the initially populated La state and also with the Lb state are placed too high energetically to partake prominently in the deactivation photo-process. The proposed mechanism present in solvated and in vacuo DNA/RNA chromophores validates the intrinsic photostability mechanism through CI-mediated non-radiative processes accompanying the bright excited-state population toward the ground state and subsequent relaxation back to the FC region.